Monitoring the skin NADH changes during ischaemia and reperfusion in humans - Niziński, Jan; Kamieniarz, Lukasz; Filberek, Piotr; Sibrecht, Greta; Guzik, Przemysław (Journal of Medical Science, 2020)
Nicotinamide adenine dinucleotide (NADH/NAD+) is involved in many important biochemical reactions in human metabolism, including participation in energy production by mitochondria. Flow Mediated Skin Fluorescence (FMSF) is a non-invasive method to study dynamic changes in the content of the reduced form of NADH by measuring the optical properties of NADH related to the emission of the autofluorescent light (460 nm) after an earlier excitation by ultraviolet light. This review summarises the available studies using this method to describe its potential and limitations.